2000
DOI: 10.1097/00002030-200004140-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sexual risk behaviour of young gay men in primary relationships: the incorporation of negotiated safety and negotiated safety compliance

Abstract: It is imperative to correct the rates of UAI with steady partners for NS and NS compliance in order to estimate accurately the rates of risky UAI. The higher rates of risky UAI found with steady partners, even after correcting for NS, support the assumption that steady relationships provide a context that facilitates sexual risk-taking behaviour. We should therefore specifically target primary relationships as a source of risk for HIV transmission, and take into consideration non-compliance with NS agreements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 12 publications
8
108
1
1
Order By: Relevance
“…When considering different sexual behaviour (anal and oral sex) related to different types of sexual partners in the last six months, similar patterns occur. As already well-established by other studies, the rates of condom use differ in relation to the kind of partners and sexual practices: protected sex with casual partners is more frequent than with a steady partner, and protected anal sex is more frequent than protected oral sex [27].…”
Section: Discussionsupporting
confidence: 56%
“…When considering different sexual behaviour (anal and oral sex) related to different types of sexual partners in the last six months, similar patterns occur. As already well-established by other studies, the rates of condom use differ in relation to the kind of partners and sexual practices: protected sex with casual partners is more frequent than with a steady partner, and protected anal sex is more frequent than protected oral sex [27].…”
Section: Discussionsupporting
confidence: 56%
“…35 Condom use has also been reported as lower among MSM partnerships that are considered "primary" than among those that are not, especially insertive UAI (46% versus 23%). 36 These behaviors have been linked to HIV acquisition; an ongoing or primary partner was reported to be the source in 50% of cases of seroconversion in a cohort of young men in Amsterdam 37 ; however, no independent confirmation of the source of infection was obtained, and many index cases reported multiple partners. In a study of 3,257 seronegative MSM in six cities, condom use was found to be significantly lower among men in a primary relationship with a single partner known or thought to be HIV-seronegative than among other men (52% vs. 14% never used condoms during receptive anal sex; 30% vs. 57% always used).…”
Section: Partnership Types Of Msmmentioning
confidence: 99%
“…[8][9][10] Negotiated safety agreements have been described among men who have sex with men (MSM) as strategies for selectively practicing condomless anal intercourse (CAI) while maintaining sexual pleasure and intimacy within relationships. [11][12][13][14][15][16][17] While intended to reduce HIV risk, such strategies may fail in practice due to factors such as inaccurate assessment of individual and partner serostatus, infrequent testing, failure to maintain the agreement, and lack of protection against STIs. [18][19][20][21] Shortcomings in assessing partner HIV risk have also been reported among heterosexuals.…”
Section: Introductionmentioning
confidence: 99%